Clinical and socio-demographic profile of treatment on osteoarthritis patients in Tirupathi, Andhra Pradesh, India - Viswanath, J.; Cheekavolu, Chakrapani; Sankaraiah, S.; Dixit, Renu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Osteoarthritis is a chronic degenerative joint disease and it is slowly progressive with signs and symptoms being pain. It is a common cause of disability affecting 60-70% of the population in the age of 60 years. It usually affects the hand, large weight bearing joints, often the knee and the hip. Methods: A prospective study was carried out in S.V Ayurvedic Medical College and Hospital. Collected the data of Socio-demographic and risk factors (age, diet, history, marital status, religion, occupation etc.) during the treatment of osteoarthritis among the patients in hospital. Results: The data reveals that majority of the patients belongs to the age group of 51-60 (43.33%) and 41-50 years (33.33%) followed by 61-70years (16.66%), 31-40 years (6.66%), and 70 % of females, 30% patients were Males in present study. 90% were married 10% were widows. 63.33% of Hindu, 23.33 % were Muslims and only 13.33% were Christians. 40%, of labour, 33.33% Businessmen, 13.33% Servicemen and 13.33% House wives. 53.33% rural, 46.66% urban area. 50% were belonging to middle class while 23.33% were very poor status, 16.66% Rich only 10 % patients were from upper middle class families. 43.33% were Primary level education, 36.66% were illiterates, 10% up to Graduation, 6.66% Post-Graduation and 3.33% up to Matriculation. 63.33% mixed diet, 36.66% vegetarian. Conclusions: Present study reveals that, incidence of osteoarthritis was very high especially in elder female, married, Hindu, labour, rural area, middle class with very poor, primary education, mixed diet (vegetarian with non-vegetarian) patients.